Non-Antimicrobial Adjuvant Therapy Using Ticagrelor Reduced Biofilm-Related Staphylococcus aureus Prosthetic Joint Infection - Narayan Pant; Narayan Pant; Socorro Miranda-Hernandez; Catherine Rush; Jeffrey Warner; Damon P. Eisen (Frontiers Media S.A., 2022)
Background: Prosthetic joint infection (PJI), frequently caused by Staphylococcus aureus, leads to a significant arthroplasty failure rate. Biofilm is a crucial virulence factor of S. aureus that is intrinsic to the pathogenesis of PJI. Biofilm-related infections are recalcitrant to antibiotic treatment. Surgical and antibiotic therapy could be combined with non-antibacterial adjuvants to improve overall treatment success. Ticagrelor, a P2Y12 receptor inhibitor antiplatelet drug, is known to have anti-staphylococcal antibacterial and antibiofilm activity. However, the molecular mechanism for ticagrelor's antibiofilm activity and its efficacy in the treatment of S. aureus PJI are unknown.Methods: To study the in vitro antibacterial and antibiofilm activity of ticagrelor, broth microdilution and crystal violet staining method were used. Ticagrelor's effect on the expression of S. aureus biofilm genes (icaA, icaD, ebps, fib, eno, and agr) was studied using the relative quantification method. To test ticagrelor's in vivo efficacy to treat S. aureus PJI, mice were randomized into five groups (n = 8/group): infected femoral implants treated with ticagrelor alone; infected implants treated with cefazolin alone; infected implants treated with ticagrelor and cefazolin; infected implants treated with phosphate buffer solution (PBS)-positive controls, and sterile implants-negative controls. Ticagrelor was administered orally from day 4 to day 7 post-surgery, while cefazolin was injected intravenously on day 7.Results: Ticagrelor, alone and with selected antibiotics, showed in vitro antibacterial and antibiofilm activity against S. aureus. Strain-specific downregulation of biofilm-related genes, fib, icaD, ebps, and eno, was shown. In an animal model of biofilm-related S. aureus PJI, ticagrelor alone and combined with cefazolin significantly reduced bacterial concentrations on the implants compared with the positive control group. Ticagrelor significantly reduced bacterial dissemination to periprosthetic tissue compared with the positive controls.Conclusion: Ticagrelor adjuvant therapy reduced S. aureus PJI in an animal model. However, this study is very preliminary to make a conclusion on the clinical implication of the findings. Based on the current results, more studies are recommended to better understand its implication.